Older adults and hackathons: a qualitative study - Kopeć, Wiesław; Balcerzak, Bartłomiej; Nielek, Radoslaw; Kowalik, Grzegorz; Wierzbicki, Adam; Casati, Fabio (2018 IEEE/ACM 40th International Conference on Software Engineering (ICSE), 2018)
Globally observed trends in aging indicate that older adults constitute a growing share of the population and an increasing demographic in the modern technologies marketplace. Therefore, it has become important to address the issue of participation of older adults in the process of developing solutions suitable for their group. In this study, we approached this topic by organizing a hackathon involving teams of young programmers and older adult participants. In our paper we describe a case study of that hackathon, in which our objective was to motivate older adults to participate in software engineering processes. Based on our results from an array of qualitative methods, we propose a set of good practices that may lead to improved older adult participation in similar events and an improved process of developing apps that target older adults.